Prioritising primary care patients with unexpected weight loss for cancer investigation: diagnostic accuracy study (update) - Nicholson, BD; Virdee, P; Aveyard, P; Price, SJ; Hobbs, FDR; Koshiaris, C; Hamilton, W (British Medical Journal Publishing Group, 2024)
Objective: To quantify the predictive value of unexpected weight loss for cancer according to patient’s age, sex, smoking status, and concurrent clinical features (symptoms, signs, and abnormal blood test results). Design: Diagnostic accuracy study (update). Setting: Data from Clinical Practice Research Datalink electronic health records linked to the National Cancer Registration and Analysis Service in primary care, England. Participants: 326 240 adults (≥18 years) with a code for unexpected weight loss from 1 January 2000 to 31 December 2019. Main outcome measures: Cancer diagnosis in the six months after the earliest weight loss code (index date). Codes for additional clinical features were identified in the three months before to one month after the index date. Diagnostic accuracy measures included positive and negative likelihood ratios, positive predictive values, and diagnostic odds ratios. Results: Of 326 240 adults with unexpected weight loss, 184 270 (56.5%) were women, 176 508 (54.1%) were aged ≥60 years, and 176 053 (54.0%) were ever smokers. 15 624 (4.8%) had a diagnosis of cancer within six months of the index date, of whom 15 051 (96.3%) were aged ≥50 years. The positive predictive value for cancer was above the 3% threshold recommended by the National Institute for Health and Care Excellence for urgent investigation in men aged ≥50 years and women aged ≥60 years. 17 additional clinical features were associated with cancer in younger men with unexpected weight loss, and eight in women. Positive likelihood ratios in men ranged from 1.43 (95% confidence interval 1.30 to 1.58) for fatigue to 21.00 (8.59 to 51.37) for rectal mass, and in women from 1.28 (1.16 to 1.41) for back pain to 19.46 (12.69 to 29.85) for pelvic mass. Abnormal blood test results associated with cancer included low albumin (positive likelihood ratio 3.24, 3.13 to 3.35) and raised platelets (3.48, 3.35 to 3.62), total white cell count (3.01, 2.89 to 3.14), and C reactive protein (3.13, 3.05 to 3.20). However, no normal blood test result in isolation ruled out cancer. Clinical features co-occurring with unexpected weight loss were associated with multiple cancer sites. Conclusion: The risk of cancer in younger adults with unexpected weight loss presenting to primary care is <3% and does not merit investigation under current UK guidelines. However, in men aged ≥50 years, women aged ≥60 years, and younger patients with concurrent clinical features, the risk of cancer warrants referral for invasive investigation. Clinical features typically associated with specific cancer sites are markers of several cancer types when they occur with unexpected weight loss. Readers’ note: This article is an updated version of a previously published BMJ paper that has since been retracted.